2010
DOI: 10.1089/jpm.2010.0355
|View full text |Cite
|
Sign up to set email alerts
|

Oncology Staff Reflections about a 52-Year-Old Staff Christmas Choir: Constructivist Research

Abstract: A staff Christmas choir supported most choir member and staff bystander respondents in an oncology hospital and is recommended in comparable contexts. Further investigation is warranted to extend understanding about Christmas music's effects in palliative care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(13 reference statements)
0
2
0
1
Order By: Relevance
“…Three-month singing interventions for patients with lung cancer have been shown to be associated with improvements in vitality, social functioning and mental health,12 while 6-month singing interventions have been shown to be associated with improvements in vitality, anxiety and overall mental health for carers and people who have been bereaved and with improvements in anxiety for patients with cancer 15. Further qualitative studies have identified improved confidence and self-esteem among people affected by cancer who sing in choirs12 as well as stress relief, friendship and feelings of reward among cancer staff 16…”
Section: Introductionmentioning
confidence: 99%
“…Three-month singing interventions for patients with lung cancer have been shown to be associated with improvements in vitality, social functioning and mental health,12 while 6-month singing interventions have been shown to be associated with improvements in vitality, anxiety and overall mental health for carers and people who have been bereaved and with improvements in anxiety for patients with cancer 15. Further qualitative studies have identified improved confidence and self-esteem among people affected by cancer who sing in choirs12 as well as stress relief, friendship and feelings of reward among cancer staff 16…”
Section: Introductionmentioning
confidence: 99%
“…A kórustagok stresszoldóként élik meg a közös tevékenységet, barátságok szövődnek és mindezek miatt egyfajta jutalomérzés alakul ki bennük. A hozzátartozók reakciói között pedig az emelkedettség, az inspiráció és a meghatottság jelent meg (O'Callaghan et al, 2009;O'Callaghan et al, 2010).…”
Section: Karácsonyi üNnepek Napjainkbanunclassified
“…The search considered key words on these subjects, both in Portuguese and in English: qualitative research, hemodynamic procedures, senses and feelings of music in cardiac catheterization, coronary angioplasty, and health. Many articles were found that referred to stress, in aspects relating to physiological and psychological functioning, in the reactions and links of cardiopathies to music therapy [2]; to depression, specifically in women [3] [4] [5]; to cancer [6] [7] [8]; to children with burns, to pain and anxiety, in the post-operatory phase, to autism and other neurological conditions [9] [10] [11] [12]; to adolescents: about anxiety, use of alcohol, refugees [13] [14] [15]; about terminal patients: cancer and religion, well-being, relaxation [16] [17]; to qualitative research, on the human body, in the expressions of dementia, identity seeking, chronic respiratory diseases; to the perception of music by the caregivers of patients in an advanced stage of cancer, to "Music Medicine" [18] [19] [20] [21], among several others, but no article referred to the use of music during hemodynamic procedures or to the senses and feelings attributed by cardiac patients to music and to the procedures.…”
Section: Introductionmentioning
confidence: 99%